Comparison of urine protein creatinine ratio and 24 hours urine protein in detecting preeclampsia - Sedhain, Nesuma; Gautam, Jageshwor; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aim: To assess the diagnostic accuracy of spot urine protein-creatinine ratio for detection of proteinuria in Preeclampsia. Methods: Cross Sectional Descriptive Study was conducted in a total of 38 pregnant women in Paropakar Maternity and Women’s Hospital in study period of 3 month. The correlation between protein- creatinine ratio in spot urine samples and urinary protein excretion in 24-hour collections were analyzed. Results: Comparison of 24 hours urinary protein and protein- creatinine ratio in women with preeclampsia shows a significant correlation (r=0.911, p<0.0001). The cut-off protein-creatinine ratios which gave maximum area under the curve for 300mg protein for 24hrs was 0.27 (sensitivity: 94.6%, specificity: 100%, PPV: 100%, NPV: 33.3%); 2000 mg urine protein excretion was 2.1 (sensitivity and specificity of 100%); 3000mg protein excreted for 24hours was 3.0 (sensitivity: 83.3%, specificity: 92.3%, PPV: 83.3%, NPV: 93.3%. Area under the ROC for 24hours urine total protein of >300mg, >2000mg and >3000mg/day were 0.946 (95%CI 0.873-1.019), 1 (95% CI 1.00-1.00) and 0.957 (95%CI 0.897- 1.016) respectively. Conclusions: Spot urine protein-creatinine ratio is as accurate as to 24 hours urine protein determination of proteinuria in Preeclampsia.